Strategi Peningkatan Kualitas Produk Ayam Geprek Rumah Makan Geprek Samsi di Kota Mataram Nusa Tenggara Barat - Safari, Muhammad Ilham; Yuarini, Dewa Ayu Anom; Harsojuwono, Bambang Admadi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
The sales of Smashed Chicken at Geprek Samsi Restaurant have remained stagnant since its establishment in 2018, with an average of 50 portions sold per day. The owner aims to increase sales to 100 portions per day. One of the main challenges in increasing sales is the high level of competition, with many food stalls and restaurants offering similar smashed chicken menus. This research aims to identify important attributes for consumers, determine the level of importance and consumer satisfaction with the quality of smashed chicken, and formulate strategies to improve product quality at Geprek Samsi Restaurant. The research method used is Quality Function Deployment (QFD) to analyze the most important product attributes for consumers. The analysis results show that the most important attributes are the taste of smashed chicken (4.58), fried chicken crispiness (4.53), smashed chicken texture (4.16), and portion size (4.08). Meanwhile, consumer satisfaction highlights that sambal variation, presentation appearance, and menu pricing are the main aspects to improve, with the highest improvement ratios being 1.35 for sambal variation, 1.30 for presentation, and 1.28 for menu price. The proposed quality improvement strategies include developing sambal variations by introducing new sambal types such as green chili sambal, shrimp paste sambal, and sambal matah. Furthermore, enhancing presentation consistency and aesthetics of the menu components is recommended. Price adjustments should also be considered to make the menu more competitive. From a technical perspective, the focus is on the process of crushing crispy chicken, frying the chicken, as well as sambal preparation and presentation, which are deemed to significantly impact product quality improvement.